2009
DOI: 10.3354/meps08264
|View full text |Cite
|
Sign up to set email alerts
|

Climate-forced seasonal mismatch between the hatching of rhinoceros auklets and the availability of anchovy

Abstract: Predator-prey relationships are key to understanding complex marine ecosystem dynamics. The match-mismatch hypothesis posits that predators time energy-intensive activities, such as reproduction, to periods of high food availability. However, predators may be constrained by various ecological or physiological processes, leading to mistimed activities relative to prey availability. We investigated inter-annual variation in the timing of breeding for a piscivorous seabird (rhinoceros auklet Cerorhinca monocerata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(40 citation statements)
references
References 45 publications
1
37
2
Order By: Relevance
“…The timing of this transition is almost certainly related to larger atmospheric processes over the northeast Pacific. Although different in detail, our observations are very similar to those of Takahashi et al (2001) and Watanuki et al (2009), who have shown that breeding success of rhinoceros auklets at Teuri Island in the northern Japan Sea is controlled by availability of energy-rich prey, brought to the colony by oceanic currents that vary with large scale atmospheric pressure differences over the North Pacific.…”
Section: Wind-driven Advectionsupporting
confidence: 78%
“…The timing of this transition is almost certainly related to larger atmospheric processes over the northeast Pacific. Although different in detail, our observations are very similar to those of Takahashi et al (2001) and Watanuki et al (2009), who have shown that breeding success of rhinoceros auklets at Teuri Island in the northern Japan Sea is controlled by availability of energy-rich prey, brought to the colony by oceanic currents that vary with large scale atmospheric pressure differences over the North Pacific.…”
Section: Wind-driven Advectionsupporting
confidence: 78%
“…Concurrently, hatching was progressively delayed at both colonies, in contrast to many other studies documenting that earlier breeding is a common response of seabirds to a warming climate (e.g. Moe et al 2009, Reed et al 2009, Votier et al 2009, Watanuki et al 2009). Delayed breeding parallel to increasing temperatures has, however, also been demonstrated for some seabird populations in both the northern (Frederiksen et al 2004, Moe et al 2009, Shultz et al 2009) and southern hemisphere (e.g.…”
Section: Discussioncontrasting
confidence: 42%
“…For seabirds, this hypothesis has been tested in a number of studies, of which many found a mismatch between predator and prey phenologies (e.g. Visser & Both 2005, Grémillet et al 2006, Watanuki et al 2009, Burthe et al 2012, but see Durant et al 2005). One general problem with the match/mismatch hypothesis, however, is that it ignores the level of food abundance, which can compensate for small mismatches in timing (cf.…”
Section: Introductionmentioning
confidence: 99%
“…Edwards & Richardson 2004). A climate-forced seasonal mismatch between the hatching of seabird chicks and the availability of prey has been detected in zooplanktivorous and piscivorous auks (Hipfner 2008;Watanuki et al 2009). …”
Section: Summary and Research Prioritiesmentioning
confidence: 99%